SUPPLIER RELATIONSHIP MANAGEMENT DALAM PENDEKATAN CONTIGENCY DAN BEST PRACTICE - Supriharyanti, Elisabeth (KINERJA, 2005)
The supplier relationship is one important type of cooperation between and among firms. Supplier relationship management (SRM) is a part of the overall supply chain management process. Over the past several years, there has been significant shift in the way organization approach supplier relationship management. Recent year have seen an increased interest and involvement in partnership model. Several authors said that partnersip will deliver superior performance. The â€œbest practiceâ€ model of supplier management is based on intepretation of the succesfull Japanese automaker Toyota. But empirical evidence suggested that the armâ€™s length model is still common inpractice. Some theoretical writing has supported a contingency approach. The paper defines conceptof SRM, theoretical foundation and shifting on SRM. This paper also presents debate from bestpractice and contingency approach.Keywords: Supplier Relationship Management, Shifting on SRM, Contigency Approach, BestPractice Approach